Development of a Parenting Education Model Based on Religious Moderation: A Qualitative Study at Madrasah Ibtidaiyah in Indonesia - Zaenal Arifin; Nur Aisyah Ramdhania (Journal of Educational Management Research, 2026)
This study aims to develop a Religious Moderation–Based Parenting Education Model in Madrasah Ibtidaiyah (MPBMB-MI) as a strategic innovation to strengthen madrasah family partnerships in improving the quality of Islamic education. The study addresses the absence of a systematic parenting education model that integrates religious moderation values within the madrasah quality assurance system. Using a Research and Development (R&D) approach, the research was conducted through needs analysis, model design, expert validation, and revision stages, with data collected through interviews, observations, and document analysis in six madrasas across four provinces in Indonesia. The findings show that parenting education programs contribute significantly to students’ character development and discipline, and that the values of religious moderation rahmah (compassion), uswah (exemplary conduct), tawashul (dialogic communication), and mas’uliyyah (spiritual responsibility)—are effectively integrated into the planning, implementation, and evaluation of parenting activities. The MPBMB-MI model achieved a high validity score of 89%, indicating that it is feasible to implement as a management-based strategy for enhancing madrasah quality through sustainable family–madrasah partnerships grounded in the principles of religious moderation.